Changing Realities for Women and Work: The Impact of COVID-19 and Prospects for the Post-Pandemic Work World - Thompson, Randal Joy; Egan, Chrys; Wu, Tina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The COVID-19 pandemic and in particular its resultant lockdown had a devastating impact on female professionals and workers in all sectors of the economy and all countries of the world. Despite their struggles and setbacks, women emerged from the pandemic with new requirements in their workplaces. This Merits Special Issue "Changing Realities for Women and Work: The Impact of COVID-19 and Prospects for the Post-Pandemic Work World" provides a multi-perspectival view of the impact of the pandemic on women and highlights some of the areas that employers need to improve in order to attract women back into the workplace. The articles included in this Special Issue highlight mental health issues exacerbated by the pandemic and the need for employers to address them; how burnout manifested during this time; the impact of the need for women to care for and educate their children in addition to working during lockdown; the importance of resilience; and career challenges women face. Successful leadership approaches among both government leaders and women themselves emerged and will be critical in the post-pandemic work world.